Combined effect of boron and salt on polypeptide resolutions in wheat (Triticum aestivum) varieties differing in their tolerance - KUMAR, ASHWANI; SHARMA, S K; LATA, CHARU; SHEOKAND, SHITAL; KULSHRESHTA, NEERAJ (The Indian Journal of Agricultural Sciences, 2015)
Salinity aggravates toxicity symptoms of boron in wheat. Four wheat (Triticum aestivum L.) varieties differing in tolerance to these stresses were subjected to five stress treatments [control (2.5 ppm B), 50 ppm B + 6 dS/m, 100 ppm B + 6 dS/m, 50 ppm B + 10 dS/m and 100 ppm B + 10 dS/m]. Higher reductions for root length, fresh and dry weight were observed in Schomburgk and HD 2009 varieties at 100 ppm B + 10 dS/m NaCl in comparison to KRL 35 and BTSchomburgk. Results indicated that combined boron and salt stresses significantly increased soluble B and proline concentrations in the roots. At the highest level of stress (100 ppm B + 10 dS/m), maximum proline accumulation was evident in HD 2009 (18.6 mg/g) and minimum in KRL 35 (13.5 mg/g). Protein profile expressions of boron tolerant and intolerant varieties of wheat showed de novo synthesis of two specific polypeptides (35.73 and 31.10 KDa) in boron tolerant variety and one (16.98 kDa) in boron intolerant variety. Likewise, KRL 35 (salt tolerant) showed 4 specific polypeptides of 89.13, 58.4, 46.21 and 31.10 kDa, whereas three specific polypeptides (24.05, 19.13 and 17.52 kDa) appeared in the salt intolerant variety (HD 2009). Appearance of 5 common polypeptides bands of MW 89.13, 53.4, 46.21. 31.10 and 25.12 kDa in both the tolerant varieties, i.e. BT-Schomburgk (boron tolerant) and KRL 35 (salt tolerant) is of special interest and could have possible use as markers for tolerance. The synthesis of common polypeptide of MW 25.12 kDa was observed in all the four varieties with increase in stress treatments.